How Office Layouts Influence Software Development? - Costa, Victor G. J.; França, César (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Background: Organizations are constantly looking for performance improvements, and office layout has been widely studied because of its hypothetical influences on the social dynamics of software engineering projects. Aim: In this article, we investigate the perceived outcomes of different workspace characteristics, from the perspective of software engineering professionals. Methods: To achieve that, we conducted a survey with software engineering practitioners, and collected data on the perceptions about their current workspaces and performance from 47 participants. We used the results of a previous systematic review to design the survey questionnaire, and focused on the four human aspects known to be influenced by the office layout. Results: Different workspace settings exhibited similar perceptions in most of the investigated factors. However, we reveal 14 items that responsible for significant differences in the performance outcomes, such as communication quality, collaboration, team learning, privacy and others. In general, open spaces were the most effective office layout to enable all these factors. Conclusions: As a conclusion, our study demonstrates that there is not a generally accepted best model for software development workspace design, as all types of setting have positive and negative aspects. Organizations that are considering investing any budget in such things as radical workspace redesign should ponder the change very carefully. Also, there is still much room for investigation in this topic.